Integrated genome based evaluation of safety and probiotic characteristics of Lactiplantibacillus plantarum YW11 isolated from Tibetan kefir - Aziz, Tariq; Naveed, Muhammad; Jabeen, Khizra; Shabbir, Muhammad Aqib; Sarwar, Abid; Zhennai, Yang; Alharbi, Metab; Alshammari, Abdulrahman; Alasmari, Abdullah F. (Frontiers in Microbiology, 2023)
The comparative genomic analysis of Lactiplantibacillus plantarum YW11 (L. plantarum YW11) isolated from Tibetan kefir involves comparison of the complete genome sequences of the isolated strain with other closely related L. plantarum strains. This type of analysis can be used to identify the genetic diversity among strains and to explore the genetic characteristics of the YW11 strain. The genome of L. plantarum YW11 was found to be composed of a circular single chromosome of 4,597,470 bp with a G + C content of 43.2%. A total of 4,278 open reading frames (ORFs) were identified in the genome and the coding density was found to be 87.8%. A comparative genomic analysis was conducted using two other L. plantarum strains, L. plantarum C11 and L. plantarum LMG21703. Genomic comparison revealed that L. plantarum YW11 shared 72.7 and 75.2% of gene content with L. plantarum C11 and L. plantarum LMG21703, respectively. Most of the genes shared between the three L. plantarum strains were involved in carbohydrate metabolism, energy production and conversion, amino acid metabolism, and transcription. In this analysis, 10 previously sequenced entire genomes of the species were compared using an in-silico technique to discover genomic divergence in genes linked with carbohydrate intake and their potential adaptations to distinct human intestinal environments. The subspecies pan-genome was open, which correlated with its extraordinary capacity to colonize several environments. Phylogenetic analysis revealed that the novel genomes were homogenously grouped among subspecies of l Lactiplantibacillus. L. plantarum was resistant to cefoxitin, erythromycin, and metronidazole, inhibited pathogens including Listeria monocytogenes, Clostridium difficile, Vibrio cholera, and others, and had excellent aerotolerance, which is useful for industrial operations. The comparative genomic analysis of L. plantarum YW11 isolated from Tibetan kefir can provide insights into the genetic characteristics of the strain, which can be used to further understand its role in the production of kefir.